Potential Health Risk Assessment for the Occurrence of Heavy Metals in Rice field Influenced by Landfill Activity in Can Tho City, Vietnam - Giao, Nguyen Thanh (International Journal of Environment, Agriculture and Biotechnology, 2020)
The study was conducted to assess potential risk of heavy metals in the soil and rice plants in the ricefield around the landfill in Dong Thang commune, Co Do district, Can Tho city, Vietnam. Four soil samples in which three samples were collected around the landfill and one sample was collected one km away from the landfill for the analysis of heavy metals including Mn, Zn, Cu, Cr, Ni, Pb and Cd. Rice samples were collected during ripening stage (few days before the harvest) at the same locations with the soil sampling, for the same heavy metal species analysis. The findings revealed that six out of seven heavy metals occurred in the soil.The decreasing order of theheavy metals concentrationsin the soil samples was Mn > Zn> Ni> Cr> Cu> Pb. This study found that accumulation of heavy metals in parts of rice at S1-S3 was higher that those at S4 (except for Zn and Pb at rice roots) and decreased in the order Mn> Zn> Cu> Ni> Cr (except in rice grain, Cr> Cu> Ni). Heavy metalsgenerally in the rice partswere in the magnitude order of root > stem-leave> grain. The calculated hazard index (HI) indicated that the accumulation of heavy metals in soil and rice grain is not likely to pose a threat to public health (HI <1), however, potential health and ecological risk may still exist. Measures should be taken to prevent landfill leachate leaching into the agricultural areas to minimize potential environmental and health risks.